Risk Microbiological Contamination in Well Water Around the Morosi Industrial Area, Southeast Sulawesi, Indonesia - Yunus, Reni; Supiati, Supiati; Darmayani, Satya; Rafika, Rafika; Ihwan, Muh.; Triyaswati, Desty (YCAB Publisher, 2025)
Background: Dug wells located near industrial areas have a higher contamination levels compared to wells far from industrial areas. Previous research has shown metal contamination in wells near industrial area. This gap highlights the need for further research that address the microbiological safety of water sources affected by industrial activities.Objectives: This study investigates the risk of microbiological contamination in well water surrounding the Morosi industrial area in Southeast Sulawesi, Indonesia.Methods: The type of research is quantitative observational design; this research analyzes 52 dug wells across four villages. Key variables examined include the distance of wells from septic tanks and the physical condition of the wells, assessed through microbiological testing using the Most Probable Number (MPN) method.Results: Majority of well samples (94.2%) did not meet microbiological quality standards, with a notable presence of E. coli in 44.2% of samples. Statistical analysis indicates a moderate relationship between the physical condition of wells and E. coli presence, as well as a significant association between proximity to septic tanks and contamination risk.Conclusion: There are various factors that contribute to the well’s contamination. Statistical analyses demonstrate the vulnerability of water sources around the Morosi industry to microbial contamination due to inadequate sanitation practices. Keywords: Microbiological contamination; dug well; Most Probable Number (MPN)